Minimal addition to the correspondence of Vincenzo Monti (Prassi Ecdotiche della Modernità Letteraria, 2019)
The contribution offers the text of seven letters of Vincenzo Monti on the basis of their autographs. The letters are all sent to Giovanni Antonio Maggi, a faithful, refined and industrious intellectual of Milan, who joined the elderly poet in almost all the latest literary labors. The three later letters were already known to scholars for some time, but are offered here in a more correct version, faithfull to the originals. The others, shorter, have remained unpublished until this publication.
Keywords: Vincenzo Monti; unpublished; letters; correspondence; original; autographs